"Covering our backs": ambulance crews' attitudes towards clinical documentation when emergency (999) patients are not conveyed to hospital. Issue 5 (23rd April 2008) - Porter, A; Snooks, H; Youren, A; Gaze, S; Whitfield, R; Rapport, F; Woollard, M
Abstract : Background: Up to 30% of people who call for an emergency ambulance are, for various reasons, not conveyed to hospital. Across the UK, the majority of ambulance services have policies and procedures requiring ambulance crews to complete clinical documentation for these patients, as they do for patients who travel to hospital. However, studies have suggested that documentation does not get completed for a large proportion of non-conveyed patients. Methods: A qualitative study in one large ambulance service trust used focus groups to explore crew members' attitudes towards clinical documentation and non-conveyed patients. Results: Considerable ambiguity was found: crews were aware of the need to "cover their backs" by completing clinical records, but at the same time expressed doubts about the value of this documentation. There appeared to be two main circumstances in which records were not completed. Firstly, there were the cases where crews may have been unable to obtain necessary information from patients who were intoxicated or otherwise uncooperative. Secondly, there were cases where the crews may not have recognised their encounter with a patient as having a clinical dimension, such as older people who had fallen but were apparently uninjured. These circumstances were combined with a lack of monitoring by managers of whether forms were being completed, and a disinclination on the part of some crew members to do what they regarded as unnecessary work. Conclusion: The low rates of completion of clinical records for non-conveyed patients appeared to result from crew members not believing they were important in every circumstance, combined with a lack of management focus. Low rates of completion may lead in turn to clinical risk and a risk of litigation if things go wrong.